2018
DOI: 10.24200/sci.2018.20327
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on natural convection of nanofluids in an inclined square enclosure with non-uniform heated walls

Abstract: Studying natural convection of nano uids in enclosures with non-uniform heated walls is of importance in many engineering applications such as solar energy collection. In this study, we developed a Fully Higher-Order Compact (FHOC) nite di erence method to investigate the natural convection and heat transfer of nano uids in an inclined square enclosure with sinusoidal temperature distributions. Numerical simulations were performed over a range of amplitude ratios, inclination angles, phase deviations, nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Hakeem et al [38] numerically investigated the second law for MHD nano uid ow over the stretching surface and showed that nanoparticles generated more entropy than non-metallic particles. Wang and Dai [39] considered natural convection of nano uid in an inclined square cavity with non-uniformly heated walls and found that at a xed Rayleigh number, average Nusselt number was higher for copper nanoparticles. Kasmani et al [40] reported the e ects of thermal radiation, Soret, and Dufour on convective heat transfer of nanoliquid over a wedge in the presence of wall suction and proved that temperature distribution enhanced by raising the values of wedge angle, radiation, Brownian motion, and thermophoresis parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Hakeem et al [38] numerically investigated the second law for MHD nano uid ow over the stretching surface and showed that nanoparticles generated more entropy than non-metallic particles. Wang and Dai [39] considered natural convection of nano uid in an inclined square cavity with non-uniformly heated walls and found that at a xed Rayleigh number, average Nusselt number was higher for copper nanoparticles. Kasmani et al [40] reported the e ects of thermal radiation, Soret, and Dufour on convective heat transfer of nanoliquid over a wedge in the presence of wall suction and proved that temperature distribution enhanced by raising the values of wedge angle, radiation, Brownian motion, and thermophoresis parameters.…”
Section: Introductionmentioning
confidence: 99%